215k views
4 votes
Type the correct answer in the box.
log +log -10823= log

Type the correct answer in the box. log +log -10823= log-example-1

2 Answers

6 votes

Answer:

log 7

Explanation:

Using the rules of logarithms

log x + log y ⇔ log (xy )

log x - log y ⇔ log (
(x)/(y) )

Given

log
(14)/(3) + log
(11)/(5) - log
(22)/(15)

= log (
(14)/(3) ×
(11)/(5) ) - log
(22)/(15)

= log (
(154)/(15) ) - log
(22)/(15)

= log (
(154)/(15) ÷
(22)/(15) )

= log (
(154)/(15) ×
(15)/(22) )

= log
(154)/(22)

= log 7

User Rushi Agrawal
by
5.4k points
6 votes
the correct answer to the equation in the picture is log 7
User Tyrelle
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.